Histopathological response and antibacterial effect of dental materials: resin vs amalgam in cavity preparations of Canis familiaris, Lambayeque 2015 - Palacios Pérez, Jany Guisella (2017)
The present investigation evidences the analysis of the compatibility of the dental tissue with the biomaterial and the consequent infections; Developing a technical procedure of valuation of these at statistical and laboratory level. The scientific problem that was considered was: What are the in - vivo differences in the histopathological response and antibacterial effect of dental materials: resin vs amalgam in the cavity preparations of Canis familiaris from the Faculty of Veterinary Medicine - Pedro National University Ruiz Gallo - Lambayeque, 2015? Presenting as hypothesis: The in - vivo difference of histopathological response and antibacterial effect of dental materials: resin vs amalgam is statistically significant in the molar cavity preparations of Canis familiaris, which was tangible in the control and experiment groups, taking as sample selected teeth from the canines. Regarding the compatibility of the biomaterial with the dental tissue, it was observed at 90 days that the bone resorption is of the active type and a greater neoformation is achieved, achieving some integration in both. There were histological changes at the apical, periodontal and bone tissue levels: when comparing experimental groups based on teeth at 30 and 60 days, there were no significant differences between the inflammatory processes (acute and chronic) in the studied groups, however It should be noted that at 90 days it was found that there are already inflammatory patterns in response to the adhesive systems applied in the cavity preparations of Canis familiaris (resin vs. amalgam) molars presenting a chronic inflammation in 100% of amalgam treated dental pieces And 25% for resin treated dental pieces; And in the case of superinfections these were not evidenced assuming an equivalent antibacterial effect for both substances.